2014
DOI: 10.2134/cm-2013-0103-rs
|View full text |Cite
|
Sign up to set email alerts
|

Granular Fertilizer Spreader Swath Uniformity Achieved at Varying Target Application Rates

Abstract: This study measured the within‐swath uniformity of both spinner and pneumatic spreaders over a range of material application rates commonly associated with precision agriculture schemes (25 to 200 lb/acre). Although small pan sampling is not appropriate for spreader rate calibration, results suggested that five of the spreaders delivered rates ranging from 50 to 200 lb/acre with reasonable accuracy. Four of the five spreaders also appeared capable of delivering an even lower rate, 25 lb/acre. Within swath coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…However, even with an acceptable distribution uniformity, a large spread width is also necessary to improve work efficiency in field applications. Studies have illustrated that a CV of 20-30% was a reasonable uniformity for granular fertilizer spreaders under some farm conditions [28,29]. Additionally, previous studies have suggested that uniformity can be as low as 5-10% and as high as 30% under actual field terrain conditions [30].…”
Section: Swath Width and Distribution Uniformitymentioning
confidence: 99%
“…However, even with an acceptable distribution uniformity, a large spread width is also necessary to improve work efficiency in field applications. Studies have illustrated that a CV of 20-30% was a reasonable uniformity for granular fertilizer spreaders under some farm conditions [28,29]. Additionally, previous studies have suggested that uniformity can be as low as 5-10% and as high as 30% under actual field terrain conditions [30].…”
Section: Swath Width and Distribution Uniformitymentioning
confidence: 99%
“…The amount variation around the average allows measuring the distribution quality. According to CROZIER & ROBERSON (2014), coefficient up to 20% is considered satisfactory.…”
Section: Coefficient Of Variation In Transverse Distributionmentioning
confidence: 99%
“…Para a escolha da faixa de aplicação adotada para cada tratamento do ensaio, após a determinação da curva de C.V. com o auxílio computacional do Adulanço 3.1, foi selecionada a maior faixa de aplicação que seguramente apresentasse C.V. de 15% em regime de tráfego alternado, medida de referência amplamente difundida na literatura (CROZIER & ROBERSON, 2014;MILAN e GALDANHA JR, 1996;YULE e PEMBERTON, 2009).…”
Section: Determinação Da Largura Da Faixa Com Base No Coeficiente De ...unclassified